2012
DOI: 10.1007/s11207-012-0156-9
|View full text |Cite
|
Sign up to set email alerts
|

The Heliospheric Plasma Sheet Observed in situ by Three Spacecraft over Four Solar Rotations

Abstract: In this paper we present in situ observations of the heliospheric plasma sheet (HPS) from STEREO-A, Wind, and STEREO-B over four solar rotations in the declining phase of Solar Cycle 23, covering late March through late June 2007. During this time period the three spacecraft were located in the ecliptic plane, and were gradually separating in heliographic longitude from about 3 degrees to 14 degrees. Crossings of the HPS were identified using the following criteria: reversal of the interplanetary magnetic fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…The HPS thickness at 1 AU was found to be below 0.01 AU by Winterhalter et al [], while larger values, in the interval [0.01,0.03] AU, were measured by Bavassano et al [] and Zhou et al []. These larger thickness values were confirmed by Foullon et al [] and Simunac et al [] with the crossing of the same HPS by three spacecraft during five solar rotations. They found that the HPS thickness does not significantly evolve on the time scale of a day but does evolve at the scale of a solar rotation, with a thickness evolving between 0.02 and 0.06 AU.…”
Section: Statistical Properties Of the Axis Orientationsupporting
confidence: 68%
“…The HPS thickness at 1 AU was found to be below 0.01 AU by Winterhalter et al [], while larger values, in the interval [0.01,0.03] AU, were measured by Bavassano et al [] and Zhou et al []. These larger thickness values were confirmed by Foullon et al [] and Simunac et al [] with the crossing of the same HPS by three spacecraft during five solar rotations. They found that the HPS thickness does not significantly evolve on the time scale of a day but does evolve at the scale of a solar rotation, with a thickness evolving between 0.02 and 0.06 AU.…”
Section: Statistical Properties Of the Axis Orientationsupporting
confidence: 68%
“…The presence of the magnetic strength, total pressure, and proton temperature increase supports the existence of this shock at this position. At the onset of the HPS, Wind experience a decline in entropy (Figure ), followed by a sharp rise during the ICME forward shock passage, before stabilizing between the shock and the second HPS boundary, due to stable density and temperature. This entropy behavior, where the increase occurs within the HPS, is rather different from the cases documented by Simunac et al (), in which an increase is reported at the second HPS boundary. We attribute this difference to the existence of the ICME forward shock within the HPS. The total pressure increased at the onset of the first HPS boundary until the ICME shock.…”
Section: Resultscontrasting
confidence: 99%
“…For further clarification, we designate the green‐shaded region as region A in Figure . This is the HPS, which has two boundaries (two vertical blue lines) identified by three main criteria: an enhancement in proton density, plasma beta enhancement, and the inversion of the interplanetary magnetic field sector (see, e.g., Crooker et al, ; Liu et al, ; Simunac et al, ; Suess et al, ; Winterhalter et al, ). For the purposes of comparison and to compensate for missing ACE data, Wind data are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…We greatly expand in this paper the study of Simunac et al [2012] by including all events observed by STEREO between 4 March 2007 and 29 February 2008. In addition, we use suprathermal electron and magnetic field data to select only those HCS events which can be considered to be a global structure.…”
Section: Discussionmentioning
confidence: 99%